2000
DOI: 10.1128/aem.66.2.518-523.2000
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene Degradation and Incorporation of Naphthalene-Derived Carbon into Biomass by the Thermophile Bacillus thermoleovorans

Abstract: The thermophilic aerobic bacterium Bacillus thermoleovorans Hamburg 2 grows at 60°C on naphthalene as the sole source of carbon and energy. In batch cultures, an effective substrate degradation was observed. The carbon balance, including naphthalene, metabolites, biomass, and CO 2 , was determined by the application of [1-13 C]naphthalene. The incorporation of naphthalene-derived carbon into the bulk biomass as well as into specified biomass fractions such as fatty acids and amino acids was confirmed by couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(96 citation statements)
references
References 24 publications
6
90
0
Order By: Relevance
“…After initial biotransformation reactions, pharmaceutical compounds are eventually broken down into central intermediates, which may explain the increased expression of genes that encode general metabolic pathway functions. This is consistent with previous studies that observed increased expression of genes in relation to amino acid metabolism, TCA cycle and oxidative phosphorylation in microbial processes degrading organic contaminants (Annweiler et al ., 2000; Li et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…After initial biotransformation reactions, pharmaceutical compounds are eventually broken down into central intermediates, which may explain the increased expression of genes that encode general metabolic pathway functions. This is consistent with previous studies that observed increased expression of genes in relation to amino acid metabolism, TCA cycle and oxidative phosphorylation in microbial processes degrading organic contaminants (Annweiler et al ., 2000; Li et al ., 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Four compounds (o-phthalic acid, 2-naphthol, 1-naphthol and protocatechuic acid) were detected directly ( Two metabolites of naphthalene degradation were identified as 1-naphthol and 2-naphthol ( Table 1), which have been described as intermediates of naphthalene degradation by B. cereus [29] and B. thermoleovorans [9]. Monohydroxylated naphthalenes could be intermediate compounds, but also a side reaction, because most of bacterial naphthalene cleavage reactions occur at the 1,2-position coursed by dioxygen- ation and dehydrogenation reactions [27].…”
Section: Identification Of Naphthalene Degradation Metabolitesmentioning
confidence: 99%
“…For enzymes assays and metabolites determination thermophilic isolate was grown in mineral salt medium (MSM) [9] 4. Batch cultures were incubated in the dark at 60°C.…”
Section: Microorganism Isolation and Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of pure cultures of naphthalene degraders have shown that approximately 20% of the carbon from added naphthalene is assimilated into bacterial biomass (Annweiler et al, 2000). Nuclear magnetic resonance analyses of pyrene-degrading bacteria also show that carbon from PAHs is assimilated into the bacterial biomass (Nieman et al, 2007), demonstrating that PAH-derived carbon is used as a carbon source, and not only respired.…”
Section: Discussionmentioning
confidence: 99%